The Effect of Example Non Example Model towards Students’ Vocabulary Mastery at the First Grade students of SMAN 4 Mataram. - Tawali Tawali (Jurnal Ilmiah Mandala Education (JIME), 2020)
This research was aimed at finding out the effect of example non example model towards students’ vocabulary mastery at the first grade students of SMAN 4 Mataram. This research was an experimental research with quasi experimental and category of this research was non-equivalent control group design. The population of this research was the first grade students of SMAN 4 Mataram consist of 210 students. The instrument that used to collect the data was test consisted of post test. The data was analysis using statistical formula of t-test. The result of data analysis showed that the value of t-test was 4.39 and t-table 2.00. So the value of t-test is higher than t-table in significance level 0.05 and degree of freedom 62-2. It meant that t-critical value was significant for this confidence level. So that way, alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Therefore, it could be concluded that there was an effect of using example non example to teach vocabulary at the first grade students of SMAN 4 Mataram.